2018
DOI: 10.1002/mgg3.342
|View full text |Cite|
|
Sign up to set email alerts
|

CBS mutations are good predictors for B6‐responsiveness: A study based on the analysis of 35 Brazilian Classical Homocystinuria patients

Abstract: BackgroundClassical homocystinuria (HCU) is a monogenic disease caused by the deficient activity of cystathionine β‐synthase (CβS). The objective of this study was to identify the CBS mutations in Brazilian patients with HCU.Methods gDNA samples were obtained for 35 patients (30 families) with biochemically confirmed diagnosis of HCU. All exons and exon‐intron boundaries of CBS gene were sequenced. Gene expression analysis by qRT‐PCR was performed in six patients. Novel missense point mutations were expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
15
0
4
Order By: Relevance
“…The CBS gene is located on the long arm of chromosome 21 with 191 variants having been described [40] (Figure 2). The most frequent pathogenic and reported mutations in different countries around the world are p.G307S (31%), and p.I278T (24%) [41,42]. The p.G307S mutation is the most prevalent CBS deficiency mutation in Ireland and Australia [6,23].…”
Section: The Most Common Cbs Reported Mutations Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…The CBS gene is located on the long arm of chromosome 21 with 191 variants having been described [40] (Figure 2). The most frequent pathogenic and reported mutations in different countries around the world are p.G307S (31%), and p.I278T (24%) [41,42]. The p.G307S mutation is the most prevalent CBS deficiency mutation in Ireland and Australia [6,23].…”
Section: The Most Common Cbs Reported Mutations Worldwidementioning
confidence: 99%
“…On the other hand, the SIFT prediction software indicated that the p.T236A and p.L230G are damaging, while the p.L72I is a tolerated mutation (17). Similarly, a total of 35 samples were obtained from Brazilian patients with a biochemically confirmed diagnosis of classical homocystinuria [42]. Eight novel mutations [c.2T>C, c.209+1delG, c.284T>C, c.329A>T, c.444delG, c.864_868delGAG, c.989_991delAGG, and c.1223+5G>T] were found.…”
Section: Recent Novel Cbs Mutationsmentioning
confidence: 99%
“…Prenatal diagnosis can be achieved by molecular genetic analyses or the extraction and culture of cells from amniotic fluid to measure CBS activity. [11,42,43] Newborn screening has been performed, especially in countries with high incidences of HCU, such as Ireland and Qatar. [44,45] The most common method is the measurement of Met in dried blood spots, but a high proportion of false negatives have been obtained by using this method.…”
Section: Diagnosismentioning
confidence: 99%
“…Ген, кодирующий СBS, расположен на плече хромосомы 21q22.3, содержит 23 экзона [5]. К развитию классической формы заболевания приводят генетиче-ские варианты в гомозиготном или компаунд-гетерозиготном состоянии [4].…”
unclassified